[RETRACTED ARTICLE]Application of Beliefs and Innovations to Support Creative Tourism Policy during the COVID - 19 Pandemic in Roi Kaen - Sarasin Area - Sittivongsa, Boonpeng (Journal of Management Science Nakhonratchasima University, 2024)
Announcement of Article Retraction The Journal of Management Science Nakhon Ratchasima Rajabhat University (JMS NRRU) has submitted a request for journal quality assessment for inclusion in the Thai-Journal Citation Index Centre (TCI) for the year 2025. During the assessment process, it was found that the article entitled: "Application of Belief and Innovation to Support Creative Tourism Policy During the COVID-19 Pandemic in the Roi Kaen Sarn Sun Area", published in JMS NRRU, Vol. 3, No. 2 (July–December 2024), pages 62–74, and authored by Boonpeng Sittiwongsa, contains significant content duplication with the following previously published articles: Mahamakut Buddhist University Roi Et Campus Journal, Vol. 12, No. 1 (January–June 2023), pages 530–540, and Journal of Organizational Management and Social Development, Vol. 3, No. 1 (2023). As a result, the editorial board of JMS NRRU hereby formally retracts the aforementioned article from JMS NRRU, Vol. 3, No. 2 (July–December 2024), pages 62–74, , to maintain academic integrity and ethical standards